IDENTIFICATION OF ETHNOMEDICAL MEDICAL PLANTS FOR DEGENERATIVE DISEASES IN TARERAN DISTRICT, SELATAN MINAHASA REGENCY, NORTH SULAWESI, INDONESIA - Ferny Tumbel; Friska Montolalu; Devitha Kalitouw (Universitas Negeri Manado, 2020)
This study aims to: Obtain distribution data and types of medicinal plants in Tareran District, South Minahasa. Obtain data on the use of medicinal plants for degenerative diseases in Tareran District, South Minahasa. Plant samples can be in the form of leaves, stems and roots or whole plants obtained in Tareran District, South Minahasa Regency. Samples of medicinal plants are devoted to medicinal plants that are used for degenerative diseases. The samples used were wet samples and dry samples (10% moisture content) and wet samples. Materials used include ethanol, alcohol, plant specimen paper, electric oven, etc. Inventory of medicinal plants using plant determination books and writing instruments, cameras and specimen boxes. Data on the use/utilization of medicinal plants using a questionnaire. The results showed that in Tareran District there are many types of plants used as medicinal plants for degenerative diseases, including: Cinnamon (hypertension), Noni (Diabetes), Temulawak (hyperlipidemia). The community has not cultivated medicinal plants intensively. Public knowledge of the scientific efficacy of medicinal plants is still very little so that it affects the utilization of these medicinal plants. In terms of the use of medicinal plants, the economically weak community uses medicinal plants more than the middle to upper economic community. In fact, there are more doubts about the efficacy of medicinal plants in the middle and upper economic community. The use of medicinal plants in the middle to upper economic community is only carried out by the elderly.